Khả năng bảo vệ xúc tác cracking trước sự tác động của kim loại nặng trong nguyên liệu khi sử dụng pha nền hoạt động là kaolin Việt Nam biến tính - Hùng và cộng sự, Lê Mạnh (Vietnam Journal of Chemistry, 2014)
Modern fluid catalytic cracking (FCC) catalysts are composed of crystalline zeolite Y which is surrounded and held together by an amorphous silica/alumina matrix. Matrix contributes significantly to the overall performance of FCC catalysts. Catalyst matrix has many of the functions such as upgrading bottoms, reducing SOx emissions, and passivating catalyst poisons. The catalyst matrix plays an important role in trapping of the heavy metal contaminants (Ni, V) in the feedstock and inhibiting their adverse effects on both catalyst activity and selectivity. Vanadium, which deposits on catalyst particles in the riser as organometallic compounds, is converted to vanadium oxides in the regenerator. In the regenerator environment, vanadium can migrate to zeolite crystals and forms a low melting eutectic with the silica-alumina of the zeolite to destroy its crystal. Continued from [1, 3], this paper inlustrates the ability to anti-poision of the cracking catalyst by these heavy metals of Vietnam modified kaolin matrix.